Detection of an Enterococcus faecium Carrying a Double Copy of the PoxtA Gene from Freshwater River, Italy - Marzia Cinthi; Sonia Nina Coccitto; Gianluca Morroni; Gloria D'Achille; Andrea Brenciani; Eleonora Giovanetti (MDPI AG, 2022)
Oxazolidinones are valuable antimicrobials that are used to treat severe infections due to multidrug-resistant (MDR) Gram-positive bacteria. However, in recent years, a significant spread of clinically relevant linezolid-resistant human bacteria that is also present in animal and environmental settings has been detected and is a cause for concern. This study aimed to investigate the presence, genetic environments, and transferability of oxazolidinone resistance genes in enterococci from freshwater samples. A total of 10 samples were collected from a river in Central Italy. Florfenicol-resistant enterococci were screened for the presence of oxazolidinone resistance genes by PCR. Enterococcus faecium M1 was positive for the poxtA gene. The poxtA transfer (filter mating and aquaria microcosm assays), localization (S1-PFGE/hybridization), genetic context, and clonality of the isolate (WGS) were analyzed. Two poxtA copies were located on the 30,877-bp pEfM1, showing high-level identity and synteny to the pEfm-Ef3 from an E. faecium collected from an Italian coastal area. The isolate was able to transfer the poxtA to enterococcal recipients both in filter mating and aquaria microcosm assays. This is-to the best of our knowledge-the first detection of an enterococcus carrying a linezolid resistance gene from freshwater in Italy.